Personal carbon trading: is now the right time? - Fawcett, T (Future Science, 2012)
Personal carbon trading (PCT) aims to reduce carbon emissions from household energy use and/or personal transport by allocating equal, tradable allowances to individuals, which will reduce over time. This article summarises the latest research into PCT and shows how it is being explored further via academic research, business and community initiatives. PCT had a moment in the UK political and policy limelight in 2007/08. Data is presented, showing how media interest has waxed and waned over the years. During the same period, research interest has persisted and grown, despite the idea’s decline in public prominence. A comparison between relevant factors in 2006/7, when the UK government was first interested in PCT, and 2011 indicates significant changes. The future prospects for PCT are assessed, together with ideas about how it could be seriously considered for implementation. Finally, there are reflections on whether now is the right time for PCT.